2000
DOI: 10.1074/jbc.275.9.6664
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of α-Crystallin-Plasma Membrane Binding

Abstract: ␣-Crystallin, a large lenticular protein complex made up of two related subunits (␣A-and ␣B-crystallin), is known to associate increasingly with fiber cell plasma membranes with age and/or the onset of cataract. To understand better the binding mechanism, we developed a sensitive membrane binding assay using lens plasma membranes and recombinant human ␣A-and ␣B-crystallins conjugated to a small fluorescent tag (Alexa350 ® ). Both ␣A and ␣B homopolymer complexes, as well as a reconstituted 3:1 heteromeric compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
115
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 44 publications
3
115
0
Order By: Relevance
“…It must be recognized that both ␣A as well as ␣B have been considered as soluble proteins of the ocular lens, yet the data presented thus far in this investigation and elsewhere (14,15,31,33,35) provide definitive evidence that both these proteins are membrane-associated. Although the exact function of ␣A remains to be elucidated, its presence in the ER has been related to ER-associated degradation of denatured proteins; it may be involved in quality control of proteins destined for the cell surface as has been recently suggested for epithelial Na (ϩ) channel expression in mouse cultured collecting duct cells (29).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It must be recognized that both ␣A as well as ␣B have been considered as soluble proteins of the ocular lens, yet the data presented thus far in this investigation and elsewhere (14,15,31,33,35) provide definitive evidence that both these proteins are membrane-associated. Although the exact function of ␣A remains to be elucidated, its presence in the ER has been related to ER-associated degradation of denatured proteins; it may be involved in quality control of proteins destined for the cell surface as has been recently suggested for epithelial Na (ϩ) channel expression in mouse cultured collecting duct cells (29).…”
Section: Discussionmentioning
confidence: 85%
“…Historically, a fraction of ␣-crystallin (both ␣A and ␣B) has been reported to be membrane-associated in the normal adult transparent lens. These observations about the association of ␣-crystallins with the membranes were first made about four decades ago (32)(33)(34)(35). We therefore examined ␣A status first in the lens epithelial explants in culture and then in the early developing lens.…”
Section: Discussionmentioning
confidence: 99%
“…The studies performed for B. japonicum sHsps reveal that heterooligomers display chaperone activities indistinguishable from homooligomeric complexes (34). In contrast, the properties of homo-and hetero-oligomeric ␣-crystallin complexes differ, because it was reported that these complexes have different lens plasma membrane-binding properties (47). It was also shown that ␣A and ␣B-crystallin homooligomers possess unique chaperone activities that are additionally differently modulated in response to temperature changes (48,49).…”
Section: Discussionmentioning
confidence: 95%
“…This ACD plays an important role in the modulation of both structural and functional properties of the HSPBs. Indeed, monomers of the HSPB proteins associate (partially via their ACDs) into dimers that are thought to act as basic units/building blocks, capable of generating oligomers ranging from ca 200 to 600 kDa [49,53]. The various HSPB monomers can form both homo-and hetero-dimers as well as Table 1.…”
Section: Introductionmentioning
confidence: 99%